OVERWEIGHT AND OBESITY IN A PUBLIC SCHOOL OF THE MUNICIPALITY OF ANÁPOLIS (CIPEEX, 2022)
INTRODUCTION: OBESITY AND OVERWEIGHT ARE DEFINED BY THE WORLD HEALTH ORGANIZATION AS AN ACCUMULATION OF EXCESSIVE OR ABNORMAL FAT THAT DAMAGES HEALTH. IT IS CAUSED BY AN IMBALANCE BETWEEN CONSUMED AND SPENT CALORIES, WHERE HIGHLY ENERGETIC FOODS ARE INGESTED TOGETHER WITH A PHYSICAL INACTIVITY OR SEDENTARY LIFESTYLE, WHICH RESULTS IN PROFILES THAT ARE NOT IN GOOD HEALTH. THE ETIOLOGY OF OBESITY IS MULTIFACTORIAL AND COMPLEX. IT MAY BE RELATED TO GENETIC FACTORS AND ENVIRONMENTAL FACTORS OF MODERNITY CURRENTLY EXPERIENCED, DUE TO THE GREAT TECHNOLOGICAL AND BEHAVIORAL INNOVATIONS THAT PRESENT INEFFECTIVE EATING PATTERNS AND SEDENTARY LIFESTYLE. THE ADOLESCENT WHO IS OBESE DURING ADOLESCENCE BECOMES AN OBESE ADULT. OBJECTIVE: TO VERIFY THE PREVALENCE OF OVERWEIGHT AND OBESITY AMONG SCHOOLCHILDREN IN A PUBLIC SCHOOL IN THE CITY OF ANÁPOLIS, GOIS, BRAZIL, AGED 10 TO 18 YEARS. DESCRIBE THE BODY MASS INDEX (BMI). DESCRIBE THE PRACTICE OF PHYSICAL ACTIVITIES. ANALYZE THE TYPE OF FEEDING PERFORMED BY THE CHILD AND ADOLESCENT POPULATION. METHODS: CROSS - SECTIONAL, PROSPECTIVE, DESCRIPTIVE STUDY WITH 113 SCHOOLCHILDREN FROM A PUBLIC COLLEGE IN ANÁPOLIS. RESULTS: WHEN ANALYZING THE SAMPLE OF THE PRESENT STUDY AND COMPARING WITH OTHER STUDIES PERFORMED IN DIFFERENT REGIONS OF THE COUNTRY, A RATE BELOW THE NATIONAL AVERAGE OF OVERWEIGHT AND OBESITY WAS OBSERVED. WITH REGARD TO EATING HABITS, THE CONSUMPTION OF FOODS CONSIDERED HEALTHY AND THE INTAKE OF WATER WERE CONSIDERED ADEQUATE. HOWEVER, THE CONSUMPTION OF FOODS CONSIDERED TO BE UNHEALTHY, THESE BEING HIGH IN SATURATED FATS, SODIUM AND SUGARS ARE HIGH, IT IS KNOWN THAT THE CONSUMPTION OF THESE FOODS IS RELATED TO THE PRE-DISPOSITION OF NON-TRANSMISSIBLE CHRONIC DISEASES, THEREFORE IT IS NECESSARY TO AWARENESS OF THE HARM OF CONSUMING THESE FOODS, AS THE HABITS ACQUIRED IN CHILDHOOD AND ADOLESCENCE WILL REMAIN IN ADULT LIFE. A SATISFACTORY FREQUENCY OF PHYSICAL ACTIVITY AND NUMBER OF DAILY MEALS WAS REPORTED BY THE STUDENTS. CONCLUSION: THE ROLE OF NURSES IN THE PREVENTION AND PROMOTION OF HEALTHY EATING THROUGH THE PRACTICE OF CONTINUING EDUCATION IN THE COMMUNITY WITHIN PRIMARY CARE AND IN PROGRAMS SUCH AS HEALTH AT SCHOOL (PSE) IS OF PARAMOUNT IMPORTANCE, USING AN INTERSECTORAL POLICY WHERE PROFESSIONALS HEALTH PROFESSIONALS TOGETHER WITH EDUCATION PROFESSIONALS SEEK MEASURES AIMED AT PROMOTING HEALTH AND PREVENTING DISEASES THAT AFFECT THE CHILD AND ADOLESCENT POPULATION.
Keywords: Obesity. Pediatric nursing. Adolescence.